Barriers in systemic delivery and preclinical testing of synthetic microRNAs in animal models: an experimental study on miR-215-5p mimic - Machackova, T; Vychytilova-Faltejskova, P; Souckova, K; Laga, R; Androvič, L; Mixová, G; Slaby, O (Physiological research, 2021)
Mus musculus is the most commonly used animal model in microRNA research; however, little is known about the endogenous miRNome of the animals used in the miRNA-targeting preclinical studies with the human xenografts. In the presented study, we evaluated the NOD/SCID gamma mouse model for the preclinical study of systemic miR-215-5p substitution with a semitelechelic poly[N-(2-hydroxypropyl)-methacrylamide]-based carrier conjugated with miR-215-5p-mimic via a reductively degradable disulfide bond. Murine mmu-miR-215-5p and human hsa-miR-215-5p have a high homology of mature sequences with only one nucleotide substitution. Due to the high homology of hsa-miR-215-5p and mmu-hsa-miR-215-5p, a similar expression in human and NOD/SCID gamma mice was expected. Expression of mmu-miR-215 in murine organs did not indicate tissue-specific expression and was highly expressed in all examined tissues. All animals included in the study showed a significantly higher concentration of miR-215-5p in the blood plasma compared to human blood plasma, where miR-215-5p is on the verge of a reliable detection limit. However, circulating mmu-miR-215-5p did not enter the human xenograft tumors generated with colorectal cancer cell lines since the levels of miR-215-5p in control tumors remained notably lower compared to those originally transfected with miR-215-5p. Finally, the systemic administration of polymer-miR-215-5p-mimic conjugate to the tail vein did not increase miR-215-5p in NOD/SCID gamma mouse blood plasma, organs, and subcutaneous tumors. It was impossible to distinguish hsa-miR-215-5p and mmu-miR-215-5p in the murine blood and organs due to the high expression of endogenous mmu-miR-215-5p. In conclusion, the examination of endogenous tissue and circulating miRNome of an experimental animal model of choice might be necessary for future miRNA studies focused on the systemic delivery of miRNA-based drugs conducted in the animal models.
Keywords: nosiče léků; Drug Carriers; Xenograft Model Antitumor Assays; Gene Expression Profiling; mikro RNA; Mice, SCID; Disease Models, Animal; Mice; MicroRNAs; Gene Transfer Techniques; modely nemocí na zvířatech; xenogenní modely - testy protinádorové aktivity; zvířata; Humans; myši inbrední NOD; technika přenosu genů; Mice, Inbred NOD; myši; stanovení celkové genové exprese; myši SCID; lidé; Animals